2012
DOI: 10.1111/j.1741-6612.2012.00618.x
|View full text |Cite
|
Sign up to set email alerts
|

Considering relocation to a retirement village: Predictors from a community sample

Abstract: The identification of factors characterising older adults seeking retirement village housing in the future is important in developing an understanding of the needs and expectations of the older population, and may allow aged care providers to better target the development of services to population needs (e.g. health-care supports). Further investigation into the specific expectations of the 55-64 year cohort is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 24 publications
2
16
0
2
Order By: Relevance
“…Previous studies have found that age, sex, the number of family members who lived together, housing type, accessibility of transportation and social connectedness were factors related to preference to move among older adults . When taken together with the present study's results, these factors appear to occur in common between middle‐aged and older adults.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Previous studies have found that age, sex, the number of family members who lived together, housing type, accessibility of transportation and social connectedness were factors related to preference to move among older adults . When taken together with the present study's results, these factors appear to occur in common between middle‐aged and older adults.…”
Section: Discussionsupporting
confidence: 75%
“…Although several studies have investigated older adults' preferences for moving, little is known about middle‐aged adults' preferences . Tang and Lee studied the expectations of adults aged over age 50 years for living arrangements, including residential relocations .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crisp et al used a survey of Australian Capital Territory residents to determine physical, psychosocial and environmental characteristics predictive of having considered moving to a retirement village. People who were retired, younger (55‐64 years), with adequate finances, poorer physical health and perceived poorer neighbourhood social cohesion were significantly more likely to have considered relocation . Respondents were also asked about the most—and least—appealing features of retirement village living that could influence their decision.…”
Section: Congregate Housing Optionsmentioning
confidence: 99%
“…The difficulties of existing settings and the attraction of new environments are influential in relocation decisions, commonly referred to as “push” and “pull” factors, respectively (Baumker et al, ; Bekhet, Zauszniewski, & Nakhla, ; Crisp, Windsor, Anstey, & Butterworth, ; Groger & Kinney, ). Pull factors may include: the potential of developing social networks; inclusion in a community of “like‐minded” people; local and accessible amenities; quality of the living environment; location and size of the complex; enhanced feelings of safety and security; the potential for increased autonomy; and access to interest groups and activities.…”
Section: Introductionmentioning
confidence: 99%